1997
DOI: 10.1073/pnas.94.16.8918
|View full text |Cite
|
Sign up to set email alerts
|

Experience-dependent, asymmetric expansion of hippocampal place fields

Abstract: Theories of sequence learning based on temporally asymmetric, Hebbian long-term potentiation predict that during route learning the spatial firing distributions of hippocampal neurons should enlarge in a direction opposite to the animal's movement. On a route AB, increased synaptic drive from cells representing A would cause cells representing B to fire earlier and more robustly. These effects appeared within a few laps in rats running on closed tracks. This provides indirect evidence for Hebbian synaptic plas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

64
434
5

Year Published

1998
1998
2014
2014

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 449 publications
(503 citation statements)
references
References 17 publications
64
434
5
Order By: Relevance
“…Non-spatial hippocampal correlates can be explained. Place cell recordings are examining detailed quantitative second-order properties of the tuning curves, including both spatial [39,112,151,174,208] (to list only a few) and non-spatial [11,94,247], and these properties are being modeled at a quantitative level [16,172,196,205]. Detailed explanations of hippocampal roles in both spatial and non-spatial tasks are available [72,173,196,225].…”
Section: Resultsmentioning
confidence: 99%
“…Non-spatial hippocampal correlates can be explained. Place cell recordings are examining detailed quantitative second-order properties of the tuning curves, including both spatial [39,112,151,174,208] (to list only a few) and non-spatial [11,94,247], and these properties are being modeled at a quantitative level [16,172,196,205]. Detailed explanations of hippocampal roles in both spatial and non-spatial tasks are available [72,173,196,225].…”
Section: Resultsmentioning
confidence: 99%
“…We conjecture that repeated pairing of different streams of input could generate robust associations between them through rapid Hebbian synaptic plasticity, resulting in stable spatial representations 48 and increased firing rates 19,[48][49][50] . Under this model, during random foraging in RW, distal visual cues are paired repeatedly with the same constellation of proximal cues at each location, resulting in a place code.…”
Section: Discussionmentioning
confidence: 99%
“…In the systematicpillar task, when we paired locomotion and visual cues repeatedly, this selectivity was strengthened and extended to the middle of the paths. Restricting the analysis to cells that fired on at least two nonoverlapping arms on the three-pillar task revealed that these cells exhibited a disto-code 21 , which is a specific case of the more general distance selectivity observed in the goal-directed tasks.We conjecture that repeated pairing of different streams of input could generate robust associations between them through rapid Hebbian synaptic plasticity, resulting in stable spatial representations 48 and increased firing rates 19,[48][49][50] . Under this model, during random foraging in RW, distal visual cues are paired repeatedly with the same constellation of proximal cues at each location, resulting in a place code.…”
mentioning
confidence: 98%
“…Our choice of such a model reflects our belief that the place-cell population represents a large scale, unitary construct, the environment, rather than an agglomeration of separate, smaller-scale features of the environment such as pairwise relationships between objects (O'Keefe and Conway 1978; Hetherington and Shapiro 1997; but see Shapiro et al 1997; Wood et al 1999). In part, this view is based on the notion that place cells (especially CA3 place cells) interact with each other and are not a set of independent feature detectors (Muller et al 1991, Muller et al 1996; Blum and Abbott 1996; Mehta et al 1997; Samsonovich and McNaughton 1997). It is our contention that connections among place cells will prove to be the essential feature that allows the place-cell ensemble to be used in navigation.…”
Section: Discussionmentioning
confidence: 99%